Dampak Pelatihan Guru dalam Mendukung Implementasi Kurikulum Merdeka di Kelas - Yudistira, Srikandi; Iriani, Umi; Hestivik, Chelsi; Andriani, Tuti (ALACRITY : Journal of Education, 2025)
Education in Indonesia has advanced rapidly through curriculum reform, including the implementation of the Merdeka Curriculum. This study aims to explore the impact of teacher training in supporting the implementation of this curriculum in classrooms. The method used is a literature review with a qualitative and descriptive approach, analyzing data from various relevant literature and academic journals. The findings indicate that teacher training plays a crucial role in enhancing pedagogical and professional competencies, as well as addressing challenges that arise during curriculum implementation. Trained teachers are better equipped to create adaptive and inclusive learning environments that support student character development. Furthermore, ongoing training helps teachers integrate technology into their teaching, thereby increasing student engagement. These findings suggest that targeted professional development efforts can significantly influence educational quality and the successful implementation of the Merdeka Curriculum.